Traumatic Brain Injury Alters Expression of Hippocampal MicroRNAs: Potential Regulators of Multiple Pathophysiological Processes - Redell, John B. (J Neurosci Res, 2009)
Multiple cellular, molecular and biochemical changes contribute to outcome after traumatic brain injury (TBI). MicroRNAs (miRNAs) are known to influence many important cellular processes, including proliferation, apoptosis, neurogenesis, angiogenesis, and morphogenesis, all processes that are involved in TBI pathophysiology. However, it has not yet been determined if miRNA expression is altered after TBI. In the present study, we used a microarray platform to examine changes in the hippocampal expression levels of 444 verified rodent miRNAs at 3 hr and 24 hr following controlled cortical impact injury. Our analysis found 50 miRNAs exhibited decreased expression levels, and 35 miRNAs exhibited increased expression levels, in the hippocampus following injury. We extended the microarray findings using quantitative PCR analysis for a subset of the miRNAs with altered expression levels (miR-107, -130a, -223, -292-5p, -433-3p, -451, -541, and -711). Bioinformatic analysis of the predicted targets for this panel of miRNAs revealed an over representation of proteins involved in several biological processes and functions known to be initiated following injury, including signal transduction, transcriptional regulation, proliferation and differentiation. Our results indicate that multiple protein targets and biological processes involved in TBI pathophysiology may be regulated by miRNAs.